PENGARUH KOMUNIKASI PEMASARAN TERHADAP MINAT PELANGGAN SHOPEE DI KOTA PALEMBANG (Lembaga Penerbitan Universitas Esa Unggul, 2022)
This study aims to determine the effect of marketing communication on the interest of Shopee customers in the city of Palembang. The population in this study are all customers who use Shopee's delivery services in Palembang City, where the exact number of customers is unknown. The number of samples taken in this study using the Lemeshow formula, this is because the total population is unknown or infinite. Based on the Lameshow formula, the number of samples was 96 people with the sampling technique used was accidental sampling. The analysis technique uses simple regression with hypothesis testing using t test. The results showed that the t arithmetic value was 4.494 > t table 1.98 and a significance value of 0.000 < = 0.05, which means that there is a significant influence between marketing communication variables and Shopee customer interest.